Normative Study of the Inconsistency of the Supreme Court Circular Letter Number 2 of 2019 with Statutory Regulations in Bankruptcy Filing by Workers - Nugraha, Lingga; Vic, Binsar Jon (Devotion : Journal of Research and Community Service, 2025)
This research is motivated by the dualism of considerations and decisions of judges in addressing bankruptcy applications filed by workers, which prompted the Supreme Court to issue Supreme Court Circular Letter Number 2 of 2019. This study aims to analyze the legal problems in terms of substance in the circular letter as a legal basis for workers filing for bankruptcy. The method used is normative legal research with a statutory and a conceptual approach. The research results indicate that there are several legal problems in the substance of the Supreme Court Circular Letter Number 2 of 2019, including inconsistencies with the concept of bankruptcy in applicable laws and regulations, potential violations of absolute authority between the Commercial Court and the Industrial Relations Court, and the emergence of a legal vacuum that has an impact on legal certainty and protection for workers as creditors. The findings of this study have significant implications for both legal practice and policy. Firstly, the inconsistency in the application of bankruptcy law for workers creates confusion and limits workers' rights, undermining their ability to access timely justice. Furthermore, the legal vacuum caused by the circular letter highlights the need for clearer legislation to align judicial practices with constitutional rights. The study calls for a revision of SEMA Number 2 of 2019 to ensure workers are granted equal legal protections and access to bankruptcy processes, strengthening their bargaining position and guaranteeing their rights as creditors. Additionally, this research could guide lawma.